Critique and Review of Time, Consumption and Everyday Life - Mohammad Abbaszadeh; Farhad Shamsi Matanagh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Among the common themes of the social sciences in Iran, the subject of time has been neglected in spite of its importance, and the poverty of the theoretical literature of sociology around time is quite evident with regard to the books and articles published. In this situation, translating this book into Persian, regardless of its translation defects, is a commendable and valuable work. The focus of this book is on the interrelationships between the concepts of time, consumption, daily life, psychological, social, and cultural factors, and the place of capitalism. Most of its articles have been written with a focus on behavioral theory and simultaneous involvement of micro and macro levels. By questioning the universal understanding of time and benefiting from comparative ethnography and historical analysis, the book is skeptical of common concepts such as traditional equilibrium and turbulent modernity. The experience of time is not shaped by external forces, but by time, being constantly reproduced and transformed by the sequence and timing of daily action. Many and probably most of the processes and actions involved in making time involve the use of things and consumption. The culture of commercial consumption plays an active role in creating value-time regimes.